2020
DOI: 10.3389/fmicb.2020.502336
|View full text |Cite
|
Sign up to set email alerts
|

Marine Microbial Food Web Networks During Phytoplankton Bloom and Non-bloom Periods: Warming Favors Smaller Organism Interactions and Intensifies Trophic Cascade

Abstract: Microbial food web organisms are at the base of the functioning of pelagic ecosystems and support the whole marine food web. They are very reactive to environmental changes and their interactions are modified in response to different productive periods such as phytoplankton bloom and non-bloom as well as contrasted climatic years. To study ecological associations, identify potential interactions between microorganisms and study the structure of the microbial food web in coastal waters, a weekly monitoring was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 96 publications
5
35
0
Order By: Relevance
“…2016 was an unusually warm year 19 , and water temperature could also have accelerated nutrient remineralisation. The present results are in accordance with those of a previous study suggesting that the warm conditions of 2016 in Thau Lagoon favoured the co-occurrence of smaller taxa, including heterotrophic nano agellates, viruses and bacteria 22 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2016 was an unusually warm year 19 , and water temperature could also have accelerated nutrient remineralisation. The present results are in accordance with those of a previous study suggesting that the warm conditions of 2016 in Thau Lagoon favoured the co-occurrence of smaller taxa, including heterotrophic nano agellates, viruses and bacteria 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Trombetta et al (2019, 2020) 19,22 found that in Thau Lagoon, water temperature triggers phytoplankton blooms and suggested that interannual warming favours interactions among small organisms and trophic cascades. The ndings of the present study suggest for the rst time that water temperature, rising from winter to spring, is the most important environmental factor regulating the composition, succession (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous decrease in growth rates of both bacterial groups with the increase in those of some phytoplankton groups observed in the present study might suggest an accentuation in competition among these groups under warming. Competition for resources among bacteria and between bacteria and phytoplankton are commonly described in natural plankton communities (Løvdal et al 2007;Trombetta et al 2020), and it was shown that warming can accentuate competition for resources (Goldman and Ryther 1976;Kordas et al 2011).…”
Section: Warming In Fall Promotes Phytoplankton and Depresses Bacterimentioning
confidence: 99%
“…Microphytoplankton are mainly represented by diatoms and dinoflagellates are generally less abundant, excepted during exceptional blooms (Derolez et al 2020b). Thus, the phytoplankton community of Thau Lagoon is generally dominated by small phytoplankton (Trombetta et al 2020). Bacteria are also highly abundant in the lagoon, their abundances ranging from 2.0 to 10.0 9 10 6 cells cm 3 (Vidussi et al 2011;Mostajir et al 2015b).…”
Section: Introductionmentioning
confidence: 99%